Implementing Quantum Search Algorithm with Metamaterials - Zhang, Weixuan; Cheng, Kaiyang; Wu, Chao; Wang, Yi; Li, Hongqiang; Zhang, Xiangdong (Advanced materials (Weinheim), 2018)
Metamaterials, artificially structured electromagnetic (EM) materials, have enabled the realization of many unconventional EM properties not found in nature, such as negative refractive index, magnetic response, invisibility cloaking, and so on. Based on these man‐made materials with novel EM properties, various devices are designed and realized. However, quantum analog devices based on metamaterials have not been achieved so far. Here, metamaterials are designed and printed to perform quantum search algorithm. The structures, comprising of an array of 2D subwavelength air holes with different radii perforated on the dielectric layer, are fabricated using a 3D‐printing technique. When an incident wave enters in the designed metamaterials, the profile of beam wavefront is processed iteratively as it propagates through the metamaterial periodically. After ≈N roundtrips, precisely the same as the efficiency of quantum search algorithm, searched items will be found with the incident wave all focusing on the marked positions. Such a metamaterial‐based quantum searching simulator may lead to remarkable achievements in wave‐based signal processors. Quantum searching metamaterials are designed and fabricated using a 3D‐printing technique. When an incident wave enters in the designed metamaterials, the profile of beam wavefront is processed iteratively as it propagates through the metamaterial periodically. After ≈N roundtrips, precisely the same as the efficiency of quantum search algorithm, searched items will be found with the incident wave all focusing on the marked positions.